Veterinary Research - Beringue, Vincent; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Aims and Scope Veterinary Research is an open access journal that publishes high-quality and novel research and review articles focusing on all aspects of infectious diseases and host-pathogen interactions in animals. The journal covers studies involving: Farmed animals, including equines, and companion animals Wild animals, when infections are of zoonotic interest and/or related to domestic animals Laboratory animals and animal models of human infectious diseases Particular attention is given to zoonotic, emerging, and re-emerging pathogens. Manuscripts based on in vitro, ex vivo, or organoid models that mimic living tissue and disease processes are also welcome. Topics of Interest The journal publishes research in the following areas: Pathogens and Host-Pathogen Interactions Novel insights into viruses, bacteria, protozoa, helminths, fungi, and mammalian prions Focus on molecular mechanisms driving host-pathogen interactions Note: Purely descriptive or correlative studies (e.g., phenotypic/genotypic antibiotic resistance surveys) are not a priority Immunity and Vaccinology Fundamental studies on systemic and mucosal immunity in infected animals Development and evaluation of new vaccines against pathogens Epidemiology, Prevention, and Control of Infectious Diseases Research enhancing our understanding of the dynamics and management of infectious diseases in animals Epidemiological contributions from veterinary sciences, computational biology, economics, social sciences, and related fields Diagnostic-Oriented Research Diagnostic-focused manuscripts may be considered on a case-by-case basis, with a preference for: Studies on serotype or variant distribution in under-reported or poorly documented regions Diagnostic data directly linked to virulence or clinical outcomes in hosts Validation of new diagnostic techniques that are broadly applicable and potentially game-changing What Is Not Within Scope Studies focused solely on treatment of diseases Pathological or clinical case reports Technical notes or incremental studies with limited originality Research for which the results apply only to a narrow geographic scope without the potential for generalisability Studies reporting negative results without significant scientific insight Review Articles and Thematic Issues Veterinary Research welcomes: Review articles offering comprehensive, critical syntheses of current knowledge in host-microbe interactions or infectious disease epidemiology. Reviews should not focus solely on the authors$1 (Bown work. Thematic issues composed of invited review articles centered on defined, relevant topics Target Audience The journal serves scientists working in: Universities and research institutes Governmental and non-governmental organizations Private companies and the pharmaceutical/veterinary industries .s
Keywords: Veterinary medicine; Virology; Microbiology; Immunology; Veterinary Science; Virology; Microbiology; Immunology